The Acquisition of Japanese Case Particles by Indonesian Learners of Japanese: Focusing on the Concept of Kou “Argument” of Verb - Maarif, Samsul (JAPANEDU: Jurnal Pendidikan dan Pengajaran Bahasa Jepang, 2023)
This research is a continuation of previous research. In previous research, the author examined the effect of the theoretical explanation of the Japanese adnominal clause on the learners’ understanding. However, in this research, it was discovered that students’ knowledge of case particles in Japanese is a key determinant of understanding Japanese adnominal clauses. In this research, the author tries to examine the effect of students’ understanding of case particles in Japanese through the concept of Kou (argument) in verbs. In line with previous research, in this research, the author also tries to bridge the theoretical concepts of linguistics so that they can be applied to Japanese language learning in the classroom. In this research, the author took 20 second-year students as a sample and divided them into two groups. In the experimental group, the author used the Focus on Form (FoF) method to teach the concept of the verb “argument” so that students could determine the correct Japanese case particles. Meanwhile, in group control, they only do pattern practice exercises like a normal class. The test analysis results of the two groups after attending the experimental class did not show any significant differences. In future research, it is necessary to look at the long-term influence of applying linguistic theory in the classroom.